Rosyjscy dziennikarze: radykalizacja przestrzeni wirtualnej - Morawicki, Jan (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
Journalism in Russia faces not only a problem of co-existence with an authoritarian regime. Intense changes within distribution of information (growth of popularity of social media, common access to video and sound recording devices, problem of fact-checking) lead to – in conditions of the present political situation – forming of specific strategies in the journalists’ behavior in the visual space, so that arises the matter of characteristic features of alterations within the following relations: employee–employer, journalist–receiver, journalist–journalist, journalist–state.